Auezov science and what is the current state, trends (Eurasian Journal of Philology Science and Education, 2019)
In the current, 2018, in the framework of the days of M.O.Auezov at the AlFarabi Kazakh NationalUniversity held scientific meetings and round tables devoted to the work of the writer.Similar events are held in other educational institutions of the country.Indeed, in his skillfully written works of art, the author left a unique wisdom that will serve as spiritualfood for future generations.Our duty is to appreciate this treasure and protect it. In this regard, «Did we know Auezov adequately?», «What is the current state, trends, advantages and disadvantages of Auezov science?» – undoubtedly these questions will always worry the readers.The following article focuses on the key points of these questions.